Media Tanam Kultur Jaringan yang Tepat untuk Perbanyakan Tanaman Pisang Cavendish (Musa acuminata L.) - Nur’riyani Nur’riyani (Bioscientiae, 2021)
There are many types of media used in tissue culture, one of which is Murashige and Skoog (MS). Growth regulators commonly used in tissue culture include Indol Acetic Acid (IAA), Naphthalene Acetic Acid (NAA), Benzyl Amino Purine (BAP), and Indole 3-Butyric Acid (IBA). The aim was to examine the effect of various types of media treatment on the growth of Cavendish banana plants. This research method was carried out by reviewing relevant articles using google until mid-2020. Based on the results of the discussion, it was shown that the most appropriate media for the process of propagation of the Cavendish banana plant was media combined with BAP and IAA hormones, because the concentrations of BAP and IAA hormones could be used. Spur the process of organogenesis in banana plantlets. In addition, giving Super Growth foliar fertilizer 1 ml / l can also stimulate root growth at the rooting stage, so that giving Super Growth is sufficient to induce the formation of shoots and plant roots. Giving coconut water concentration of 7.5% and 15% into the planting medium can produce the best shoot initiation and the number of banana shoots.